Impact of colibacillosis on production in laying hens associated with interference of the phosphotransfer network and oxidative stress - da Rosa G.* (2019)
© 2019 Elsevier LtdThe objective of this study was to evaluate the productive impact of colibacillosis on laying hens and to investigate whether energetic metabolism and oxidative stress were involved in the pathogenesis of the disease. An experimental shed containing 270 laying hens of the Hy-Line lineage (32 weeks old) presented approximately 40% daily laying, and many birds presented with diarrhea and apathy followed by death. Necropsy revealed macroscopic lesions compatible with colibacillosis and infectious agent Escherichia coli was isolated from fecal samples of all birds in the infected group, as well as from tissue (ovary, liver and peritoneum). Sixteen chickens were selected for this study, divided into two groups: Control (animals without clinical alterations) and infected (with diarrhea and apathetic). E. coli isolates were subjected to the antimicrobial susceptibility testing according to the methodology approved by CLSI, 2018. This testing showed sensitivity to gentamicin, amoxicillin, norfloxacin and colistin. It was then determined that laying hens would be treated with norfloxacin (15 mg/kg) diluted in water offered at will to the birds for three days. Blood collections were performed via brachial vein after the diagnosis of E. coli (before starting treatment) and seven days after treatment. Three debilitated chickens died on the second day after initiating therapy. Before treatment, birds with clinical signs had higher levels of lipoperoxidation (LPO) and activities of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) than in the control group (asymptomatic animals). After treatment, LPO levels remained higher in birds that had clinical disease (infected group), whereas the activity of SOD and GPx enzymes did not differ between groups. Activity levels of creatine kinase (CK) and pyruvate kinase (PK) were higher in the group of chickens with clinical disease before treatment. Post-treatment, no differences were observed between groups in terms of CK; however, PK activity remained high in these animals. In the hens that died, there were lesions characteristic of avian colibacillosis, with ovary involvement, explaining the low laying activity of the birds at their peak of production. For 10 days after starting treatment, the percentage of laying increased to 90%. Therefore, we conclude that colibacillosis interferes with the phosphotransfer network by stimulating ATP production, in addition to causing oxidative stress of the birds during laying, that negatively affects health and productive efficiency.